Geographical classification of Java Tea (Orthosiphon stamineus) from Java Island by FTIR Spectroscopy Combined with Canonical Variate Analysis - Mohamad Rafi; Edy Djauhari Purwakusumah; Taopik Ridwan; Baba Barus; Atang Sutandi; Latifah Kosim Darusman (JURNAL SAINS DAN MATEMATIKA, 2015)
FTIR spectroscopy combined with canonical variate analysis was used for differentiation of java tea (Orthosiphon stamineus) according to their geographical origin. FTIR spectra of all java tea samples were acquired in the mid infrared region (wavenumber range 4000-400 cm-1). Preprocessing signal of FTIR spectra has been carried out prior to canonical variate analysis by standard normal variate. Combination of FTIR spectra in the region 1800-900 cm-1with canonical variate analysis has the power to differentiate java tea samples in terms of geographical origin. The developed method could be used for identification of geographical origin of java tea based on the samples used in this study.